2022
DOI: 10.1080/21655979.2022.2036909
|View full text |Cite
|
Sign up to set email alerts
|

Bupivacaine modulates the apoptosis and ferroptosis in bladder cancer via phosphatidylinositol 3-kinase (PI3K)/AKT pathway

Abstract: The study aimed to explore the effects of local anesthetic bupivacaine on bladder cancer cells in vivo and in vitro . The cytotoxicity was detected by MTT assay. Apoptosis was measured by Hoechst 33342 staining and TUNEL. The contents of Fe 2+ , Malondialdehyde (MDA), Glutathione (GSH) and reactive oxygen species (ROS) were evaluated by the corresponding kit. Mitochondrial membrane potential was assessed by JC-1 kit. HE staining, TUNEL and im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…In addition, the rescue of anisomycin-induced cell death by SB203580 was limited, because anisomycin (AN in figure) is a multifunctional drug that kills cells through multiple targets [ 77 81 ]. Moreover, several studies demonstrated that SB203580 could inhibit AKT, and the inhibition of AKT was involved in the induction of ferroptosis and apoptosis [ 82 84 ]. We cannot definitively rule out their roles in anisomycin-induced ferroptosis, but we can identify a major role for p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the rescue of anisomycin-induced cell death by SB203580 was limited, because anisomycin (AN in figure) is a multifunctional drug that kills cells through multiple targets [ 77 81 ]. Moreover, several studies demonstrated that SB203580 could inhibit AKT, and the inhibition of AKT was involved in the induction of ferroptosis and apoptosis [ 82 84 ]. We cannot definitively rule out their roles in anisomycin-induced ferroptosis, but we can identify a major role for p38 MAPK.…”
Section: Discussionmentioning
confidence: 99%
“…Epithelial membrane protein 1 (EMP1) was found to be downregulated in BC cells. In cells lacking EMP1, the addition of the ferroptosis inducer erastin promoted anti-ferroptosis cell death through upregulation of SLC7A11 expression ( Hao et al, 2022 ). Thus, OUTB1 and EMP1 may be potential therapeutic targets.…”
Section: The Role Of Ferroptosis In Bladder Cancermentioning
confidence: 99%
“…Bupivacaine (0.25–16 mM), a common local anesthetic, was found to inhibit PI3K/AKT signaling pathway activity by increasing Fe 2+ levels and ROS levels. Furthermore, it reduced GSH levels and increased malonaldehyde (MDA) levels in BC cells, which suppressed the growth of xenografted tumors and induced ferroptosis ( Hao et al, 2022 ).…”
Section: Potential Therapeutic Drugsmentioning
confidence: 99%
“…At the protein level, bupivacaine inhibited the expression of solute carrier family 7 members 11 (SLC7A11; also commonly known as xCT) and GPX4 while increasing ROS levels. Further results showed that bupivacaine decreased mitochondrial membrane potential, decreased GSH, increased MDA levels, and attenuated the phosphorylation of PI3K, Akt, and mTOR ( Hao et al, 2022 ). These data suggest that bupivacaine promotes ferroptosis in bladder cancer cells.…”
Section: The Effect Of Anaesthetics On Ferroptosismentioning
confidence: 99%
“…Etomidate inhibits ischaemia/reperfusion (I/R)-induced ferroptosis through the Nrf2 pathway and alleviates myocardial injury, which may supply a fresh idea for clinical reperfusion therapy ( Lv et al, 2021 ). For cancerous cells, anaesthetics such as bupivacaine, propofol, and ketamine can induce ferroptosis and play an anticancer effect ( He et al, 2021 ; Hao et al, 2022 ; Liu et al, 2021a ). In an ALI model, both sevoflurane and DEX inhibited cellular ferroptosis and protected lung function ( Liu et al, 2021b ; Lin et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%